Modeling Digital Preser vation Capabilities in Enterprise Architecture - Becker, C. (2011)
The rising awareness of the challenges of preserving information over the long term has led to a wealth of initiatives developing economic models, methods, tools, systems, guidelines and standards for digital preservation. The challenge of digital preservation is to assure that information nowadays coded and stored in digital formats can be read and be used in an unforeseen future. This is an interdisciplinary problem combining organizational and technical challenges. However, to date there is no unified view on how to approach the problem from a holistic perspective and align organizational and technical issues in a systems engineering approach. Organizations that aim to add digital preservation to their abilities generally have difficulties to assess their existing systems and what capabilities and components they are missing in order to address the needs of trustworthy information longevity. In this paper we present an approach that enables us to accommodate the concerns of digital preservation in Enterprise Architecture practice. We discuss key elements of a generic reference architecture for digital preservation and a capability model based on established domain-specific reference models. Distilling these knowledge sources into a consistent and coherent view allows baseline assessment and incremental capability development in typical IT governance scenarios where an IT architecture already exists. We illustrate this with the assessment of a government agency's existing capabilities and systems against emerging digital preservation requirements.